Which equation is equivalent to the equation below, when solved for y?
2(x + y) - z = 2x + z
A.) y = 1
B.) y = z
C.) y = 1 + 4x
D.) y = z + 4x
Solve the equation x² + 6x = -11/4
A.) x = -3 and 2
B.) x = -2 and 3
C.) x = 1/2 and -11/2
D.) x = -1/2 and -11/2
A ball was thrown upward into the air. The height in feet of the ball, above the ground, t seconds after being thrown
can be determined by the expression -16t² + 40t + 3. What is the meaning of the 3 in the expression.
A.) the ball took three seconds to reach its maximum height
B.) the ball took three seconds to reach the ground
C.) the ball was thrown from a height of three feet
D.) the ball reached a maximum height of three feet
Emerson has $120. Each week he saves an additional $15. Write a function f(x) that models the total amount
of money Emerson has after x weeks.
An equation is shown.
16x² + 10x - 27 = -6x + 5
What are the solutions to the equation?
Casey asks a random sample of students at his high school about their natural hair and eye colors. The results of his
survey are shown in the relative frequency table.
In the sample, there are 4 more students with brown hair and blue eyes than blonde hair and blue eyes.
How many total students have black hair?
A system of equations is given.
y = x² - 9
y = -2x - 1
What is one solution to the system?
Algebra 1 State Test Practice Archives